Antiangiogenic Therapy for High-Grade Gliomas - Chamberlain, Marc C.; Raizer, Jeff (CNS & Neurological Disorders - Drug Targets, 2009)
Background: Gliomas and in particular high-grade gliomas (HGG) demonstrate when compared to other nonneural solid cancers amongst the highest levels of tumor angiogenesis (the formation of new blood vessels from preexisting vasculature). Methods: Angiogenesis is a common theme in cancer biology and reflects the requirement of a vascular network to support continued uncontrolled cancer growth. Early recognition of this paradigm suggested a potential and novel cancer treatment target that led to the discovery and implementation of antiangiogenic therapies. Two basic strategies of cancer antiangiogenic therapy have emerged, one targeting vascular endothelial growth factor, VEGF (growth factor ligandbased antagonists) and the second targeting the vascular endothelial growth factor receptor, VEGFR (receptor-based antagonists, small molecule tyrosine kinase inhibitors). Emerging literature suggests efficacy of antiangiogenic therapy for recurrent HGG. Results: Notwithstanding the limited literature regarding the treatment of recurrent HGG with antiangiogenic therapy (predominantly ligand-based and administered in conjunction with cytotoxic chemotherapy), this therapy has become the de facto standard of care for many. Response rates vary from 30-60% and 6-month progression free survival varies from 25-50%. Problematic however are new antiangiogenic class side effects (hypertension, fatigue, proteinuria, intratumoral hemorrhage, arterial thrombosis and wound dehiscence), timing in relationship to surgery, measurements of response, lack of established dose response relationships and pharmacoeconomics and a possible change in tumor biology. Conclusions: Ligand-based antiangiogenic therapy (in particular bevacizumab) is a compelling new targeted therapy for HGG and will continue to emerge as an important novel anti-glioma therapy. Further studies are required to define the population of patients with HGG in whom this therapy is of benefit, identify the optimal dose and schedule, better characterize the value of co-administered (cytotoxic and targeted) therapies and establish validated response measures.
Keywords: High-grade gliomas